The effects of resistance exercise on appetite sensations, appetite related hormones and energy intake in hormone receptor-positive breast cancer survivors. (1st March 2023) - Purcell, Sarah A.; Melanson, Edward L.; Afghahi, Anosheh; Borges, Virginia F.; Sinelli, Isabella; Cornier, Marc-Andre
Abstract: Appetite is a determinant of dietary intake and is impacted by sex hormones, exercise, and body composition among individuals without chronic conditions. Whether appetite is altered by exercise in the context of estrogen suppression and cancer survivorship is unknown. This randomized cross-over study compared appetite and ad libitum energy intake (EI) after acute resistance exercise (REx) versus sedentary (SED) conditions and in relation to body composition and resting metabolic rate (RMR) in breast cancer survivors (BCS). Physically inactive premenopausal females with previous stage I-III estrogen receptor-positive breast cancer completed a single bout of REx or SED 35 minutes after a standardized breakfast meal. Appetite visual analog scales and hormones (total ghrelin and peptide-YY [PYY]) were measured before and 30, 90, 120, 150, and 180 minutes post-meal and expressed as area under the curve (AUC). Participants were offered a buffet-type meal 180 minutes after breakfast to assess ad libitum EI. Body composition (dual X-ray absorptiometry) and RMR (indirect calorimetry) were measured during a separate visit. Sixteen BCS were included (age: 46 ± 2 y, BMI: 24.9 ± 1.0 kg/m 2 ). There were no differences in appetite ratings or EI between conditions. There were no differences in appetite hormone AUC, but REx resulted in lower ghrelin 120 (−85 ± 39 pg/mL, p = 0.031) and 180 (−114 ± 43 pg/mL, p = 0.018) minutes post-breakfast and higher PYY 90 (21 ± 10 pg/mL, p = 0.028) and 120 (14 ± 7 pg/mL, p = 0.041) minutes post-breakfast. Fat-free mass and RMR negatively correlated with hunger and prospective food consumption AUC after SED, but not REx. In sum, a single REx bout temporarily reduces orexigenic and increases anorexic appetite hormones, but not acute subjective appetite sensations or EI.